2013
DOI: 10.1007/s00296-013-2740-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of single nucleotide polymorphisms in the calcitonin gene with primary osteoarthritis of the knee in Mexican mestizo population

Abstract: Primary osteoarthritis (OA) is a multifactorial disorder with several genetics factors involved. Calcitonin (CT) has been suggested to possess chondroprotective effects and could play an important role in the pathogenesis of OA. The aim of this study was to investigate whether genetic variations in or adjacent to the CT gene may be associated with primary OA of the knee in Mexican mestizo population. We conducted a case-control study to investigate the association between six single nucleotide polymorphisms at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…35 In addition to the classical predisposing factors listed here, several studies have demonstrated that gene polymorphisms may be related to the pathogenesis of OA. 6–8…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In addition to the classical predisposing factors listed here, several studies have demonstrated that gene polymorphisms may be related to the pathogenesis of OA. 6–8…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In addition to the classical predisposing factors listed here, several studies have demonstrated that gene polymorphisms may be related to the pathogenesis of OA. [6][7][8] Currently, with limited diagnostic approaches, the major treatment of OA is to control the inflammation while managing the patient's pain. The administration of Bradykinin B2 receptor (BDKRB2) antagonists, which reportedly produce enduring analgesic effects in patients afflicted with OA of the knee, signifies the potential key role played by bradykinins in the progression of the disease.…”
Section: Introductionmentioning
confidence: 99%